Association analysis of potentially functional variants within 8p12 with schizophrenia in the Han Chinese population. (2nd January 2021) - Chen, Ruirui; Chen, Jianhua; Gao, Chengwen; Wu, Chuanhong; Pan, Dun; Zhang, Jinmai; Zhou, Juan; Wang, Ke; Zhang, Qian; Yang, Qiangzhen; Jian, Xuemin; Zhao, Yalin; et al.
Abstract: Objectives: Chromosome 8p12 was first identified as a schizophrenia (SCZ) risk locus in Chinese populations and replicated in European populations. However, the underlying functional variants still need to be further explored. In this study, we sought to identify plausible causal variants within this locus. Methods: A total of 386 potentially functional variants from 29 genes within the 8p12 locus were analysed in 2403 SCZ cases and 2594 control subjects in the Han Chinese population using Affymetrix customised genotyping assays. SHEsisplus was used for association analysis. A multiple testing corrected p value (false discovery rate (FDR)) < .05 was considered significant, and an unadjusted p value < .05 was considered nominal evidence of an association. Results: We did not find significant associations between the tested variants and SCZ. However, nominal associations were found for rs201292574 (unadjusted p  = .033, FDR p  = .571; 95% confidence interval (CI): 0.265–0.945; TACC1, NP_006274.2:p.Ala211Thr) and rs45563241 (unadjusted p  = .039, FDR p  = .571; 95% CI: 1.023–1.866; a synonymous mutation in ADRB3 ). Conclusions: Our results provide limited evidence for the associations between variants from protein coding regions in 8p12 and SCZ in the Chinese population. Analyses of both coding and regulatory variants in larger sample sizes are required to further clarify the causal variants for SCZ with this risk locus.